Robot-integrated intraoperative ultrasound: Initial experience with hepatic malignancies. Issue 6 (2nd November 2015) - Guerra, Francesco; Amore Bonapasta, Stefano; Annecchiarico, Mario; Bongiolatti, Stefano; Coratti, Andrea
Abstract: Purpose: A new robotic surgery tool allows intraoperative ultrasound to be performed using a fully robotic technique. Herein, we evaluate the feasibility and reliability of robotically integrated ultrasound to guide resection of malignant hepatic tumors.Material and methods : A consecutive series of ultrasound-guided robotic resections of primary and secondary hepatic malignancies was analyzed in terms of perioperative data and specimen evaluation, focusing on the reliability of the new robot-integrated ultrasound probe.Results : Ten consecutive patients underwent 15 robotic liver resections. Two patients were resected to excise primary hepatocellular cancers and eight underwent resections of liver metastases. R0 resections were achieved for all lesions. The median operative time was 247 min, and blood loss was limited. No mortality occurred.Conclusions : Our present analysis confirmed the reliability of fully robotic liver resection guided via robotically integrated ultrasonic assessment. Robotic surgery, particularly hepatic resection, may benefit greatly from better manageability, and the fact that the surgeon can directly manage both the operative and the diagnostic parts of the procedure.